Criminality derived from natural disasters: proposal for the creation of public policy (2014)
The present study based on documentary review and review of secondary and primary sources analyze the criminality linked to natural disasters, in order to generate lines of action that contribute to reduce the risk of committing crimes in emergency and while natural disaster occurs. It considering the explanation of criminal conduct, and then understanding the criminal genesis and the criminal dynamic issued from situations of vulnerability prior to a disaster.. Two types of the crime are described: crime as meeting basic needs and crime with a goal in itself. Moreover, this shows the importance of having public policies or criminal policies in the country applicable in cases of natural disasters with emphasis on the safety and stability of the region.